Nitrogen and phosphorus significantly alter growth, nitrogen fixation, anatoxin-a content, and the transcriptome of the bloom-forming cyanobacterium, Dolichospermum - Kramer, Benjamin J.; Jankowiak, Jennifer G.; Nanjappa, Deepak; Harke, Matthew J.; Gobler, Christopher J. (Frontiers in Microbiology, 2022)
While freshwater cyanobacteria are traditionally thought to be limited by the availability of phosphorus (P), fixed nitrogen (N) supply can promote the growth and/or toxin production of some genera. This study characterizes how growth on N2 (control), nitrate (NO3-), ammonium (NH4+), and urea as well as P limitation altered the growth, toxin production, N2 fixation, and gene expression of an anatoxin-a (ATX-A) - producing strain of Dolichospermum (sp. 54). The transcriptomes of fixed N and P-limited cultures differed significantly from those of fixed N-deplete, P-replete (control) cultures, while the transcriptomes of P-replete cultures amended with either NH4+ or NO3- were not significantly different relative to those of the control. Growth rates of Dolichospermum (sp. 54) were significantly higher when grown on fixed N relative to without fixed N; growth on NH4+ was also significantly greater than growth on NO3-. NH4+ and urea significantly lowered N2 fixation and nifD gene transcript abundance relative to the control while cultures amended with NO3- exhibited N2 fixation and nifD gene transcript abundance that was not different from the control. Cultures grown on NH4+ exhibited the lowest ATX-A content per cell and lower transcript abundance of genes associated ATX-A synthesis (ana), while the abundance of transcripts of several ana genes were highest under fixed N and P - limited conditions. The significant negative correlation between growth rate and cellular anatoxin quota as well as the significantly higher number of transcripts of ana genes in cultures deprived of fixed N and P relative to P-replete cultures amended with NH4+ suggests ATX-A was being actively synthesized under P limitation. Collectively, these findings indicate that management strategies that do not regulate fixed N loading will leave eutrophic water bodies vulnerable to more intense and toxic (due to increased biomass) blooms of Dolichospermum.